ANALISIS SEMIOTIKA PADA PUISI “IBUNDA” KARYA WS. RENDRA - Lia Sulistiawati; Intan Sari Ramdhani (Lembaga Pengembangan Kinerja Dosen, 2023)
Poetry is a literary work that contains the expression of the author's heart. Made using beautiful language, it contains meaning, rhythm, rhyme, dimensions and stanzas. Poetry has two main building structures, namely the inner structure and the physical structure. The poem contains several signs, both meanings that must be interpreted directly by the reader, as well as linguistic signs that do not require redefinition. The field that studies and examines signs, symbols and signs is called semiotics. Semiotics is a science or analytical method that studies signs in language or literary works, both linguistic and non-linguistic, with the aim of understanding the meaning to be conveyed by the author as a whole. Language is a complete and perfect sign system. Therefore, language represents something meaning. A semiotic study on the poem